Identification of transmission foci of Schistosoma mansoni: narrowing the intervention target from district to transmission focus in Ethiopia - Abebaw Tiruneh; Daniel Kahase; Endalew Zemene; Eyob Tekalign; Absra Solomon; Zeleke Mekonnen (BMC Public Health, 2020)
Abstract Background Schistosoma mansoni (S. mansoni) infection is a significant public health problem in Ethiopia, and has wide distribution in the country. The impact of the disease is particularly high on school-age children. Nationwide 385 endemic districts were identified, whereby control and elimination interventions are underway using school-based annual mass drug administration (MDA) with praziquantel. The national elimination program targets endemic districts as a whole. The aim of this study was to identify the transmission foci of Schistosoma mansoni and determine prevalence of soil-transmitted helminths (STHs) in Abeshge district. Methods The study was conducted from April to May, 2019 among school-age children randomly selected from public elementary schools in Abeshge district, South-central Ethiopia. Demographic information and data on risk factors of S. mansoni infection were gathered using pre-tested questionnaire. Moreover, a stool sample was collected from each child and examined using Kato-Katz thick smear technique. The data were analyzed using STATA_MP version 12. Results A total of 389 school-age children from five public elementary schools were included in the study. The overall prevalence of S. mansoni and STHs was 19.3% (75/389) and 35% (136/389), respectively. The prevalence of S. mansoni was 60.6% in Kulit Elementary school, while it was zero in Geraba. The prevalence of S. mansoni was significantly higher among males (AOR = 2.6, 95% CI 1.3–5.1), those with habit of swimming and/or bathing in rivers (AOR = 2.9, 95%CI 1.3–5.1) and involved in irrigation activities (AOR = 2.9, 95% CI 1.0–8.3). Overall, the prevalence of S. mansoni was significantly higher among school children attending Kulit Elementary School compared to those attending the remaining schools (AOR = 12.5, 95%CI 6.2–25.1). Conclusion A wide variation of S. mansoni prevalence was observed among the school children in the different schools. Control interventions better identify and target foci of S. mansoni transmission, instead of targeting the district homogenously.